ANALYSIS OF POLITENESS STRATEGIES USED IN LT. WATERS’ DIRECTIVE UTTERANCES IN THE FILM TEARS OF THE SUN - Ridha, Fuad; Rahayu, Puji Sri (English Department of Faculty of Tarbiyah and Teacher Training, 2015)
The problem formulations of this research are what the kinds of the politeness strategies are used in Lt. Waters? directive utterances in the film Tears of the Sun and what kind of politeness strategies most frequently used in Lt. Waters? directive utterances in the film Tears of the Sun. This research aims to determine the kinds of the politeness strategies used in Lt. Waters? directive utterances in the film Tears of the Sun and to find the kind of politeness strategies are most frequently used in Lt. Waters? directive utterances in the film Tears of the Sun. The result of this research states that the researcher found that there are 127 directive utterances used by Lt. Waters in the film Tears of the Sun. In this research, the researcher can conclude that all politeness strategies based on Brown and Levinson Theory were applied by Lt. Waters in his directive utterances. The researcher found out that directive utterance in bald on record is the most frequently used. There are 86directive utterances and the most reason is Powerful Speaker.